Fabrication, properties and application of Ge-on-GaAs thin nanoheterogeneous films - Venger, E. F.; Lytvyn, P. M.; Matveeva, L. A.; Mitin, V. F.; Kholevchuk, V. V. (Technology and design in electronic equipment, 2014)
Ge thin films condensation in vacuum onto semiinsulating GaAs(100) substrates was investigated. The methods of atomic-force microscopy, optical spectroscopy, measurement of intrinsic mechanical stresses in film, and electronic properties were used for this investigation. It was found that it is possible to obtain thin nanoheterogeneous monocrystalline dislocation-free films with low intrinsic mechanical stresses and two-dimension percolation-type conductivity, as well as high temperature sensitivity that can be used for IR and electronics technologies.